Myeloid Fbxw7 Prevents Pulmonary Fibrosis by Suppressing TGF-β Production - He, Jia; Du, Yue; Li, Gaopeng; Xiao, Peng; Sun, Xingzheng; Song, Wenjun; Lai, Lihua; Xia, Meng; Zhang, Jianhua; Wang, Qingqing (Frontiers in Immunology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a group of chronic interstitial pulmonary diseases characterized by an inexorable decline in lung function with limited treatment options. The abnormal expression of transforming growth factor-β (TGF-β) in profibrotic macrophages is linked to severe pulmonary fibrosis, but the regulation mechanisms of TGF-β expression are incompletely understood. We found that decreased expression of E3 ubiquitin ligase Fbxw7 in peripheral blood mononuclear cells (PBMCs) was significantly related to the severity of pulmonary fibrosis in IPF patients. Fbxw7 is identified to be a crucial suppressing factor for pulmonary fibrosis development and progression in a mouse model induced by intratracheal bleomycin treatment. Myeloid cell-specific Fbxw7 deletion increases pulmonary monocyte-macrophages accumulation in lung tissue, and eventually promotes bleomycin-induced collagen deposition and progressive pulmonary fibrosis. Notably, the expression of TGF-β in profibrotic macrophages was significantly upregulated in myeloid cell-specific Fbxw7 deletion mice after bleomycin treatment. C-Jun has long been regarded as a critical transcription factor of Tgfb1, we clarified that Fbxw7 inhibits the expression of TGF-β in profibrotic macrophages by interacting with c-Jun and mediating its K48-linked ubiquitination and degradation. These findings provide insight into the role of Fbxw7 in the regulation of macrophages during the pathogenesis of pulmonary fibrosis.